The Effect of Just in Time and Total Quality Management on Managerial Performance (Case Study on 13 Shrimp Ponds of Lebak Regency) - Sari, Gina Nikita; Ahmad, Afridian Wirahadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the impact of Just-In-Time (JIT) and Total Quality Management (TQM) on managerial performance in the Paguyuban Shrimp Farming Company, Lebak Regency. The variables studied were managerial performance (Y), JIT (X1), and TQM (X2), involving 52 pond managers from 13 ponds as a census sample. Data collection methods included questionnaires, observations, and interviews, analyzed using SmartPLS 4.0. The study found that JIT positively and significantly affects managerial performance, with a parameter coefficient of 0.533 and a statistical T-value of 4.873 (>1.96, P=0.000). Conversely, TQM showed a negative and negligible effect, with a parameter coefficient of -0.018 and a statistical T-value of 0.125 (<1.96, P=0.900). Together, JIT and TQM significantly influence managerial performance, as indicated by a combined P-value of 0.000 (<0.05).